Positive Youth Development and Mental Well-Being in Late Adolescence: The Role of Body Appreciation. Findings From a Prospective Study in Norway - Urke, Helga Bjørnøy; Holsen, Ingrid; Larsen, Torill (Frontiers in Psychology, 2021)
Although a vulnerable period, adolescence is a time of great potential for healthy development. Understanding factors that contribute to mental well-being in this period is of great importance to facilitate for healthy development. During the adolescence period the body goes through rapid and considerable changes, and the focus on body appearance and perfection is substantial at societal, media, and peer level. In this study, we investigated the association between dimensions characterizing positive youth development, and mental well-being among Norwegian adolescents 16–17 years 1 year later, and whether this association was mediated by degree of body appreciation. We further tested whether the indirect and direct paths between positive youth development dimensions and mental well-being were moderated by gender. We used data from the first and second follow-up of the control arm of the COMPLETE study, a cluster randomized controlled trial in upper secondary schools in Norway. Findings showed that positive youth development in grade 1, as measured by both a combined global PYD and the dimensions competence, and connection were significantly associated with mental well-being in grade 2 in models adjusted for mental well-being in grade 1, gender and perceived family affluence. Also, body appreciation in grade 1 significantly predicted mental well-being in grade 2 in models including each of global PYD, competence, connection, character, and caring dimensions. Contrary to our hypothesis, no mediating effects of body appreciation were observed, and no moderation of indirect effects by gender were observed.